The Universe, Life and Everything... Dialogues on our Changing Understanding of Reality - Durston, Sarah; Baggerman, Ton; Project Muse; Project Muse. (Project Muse, 2020)
Our current understanding of our world is nearly 350 years old. It stems from the ideas of Descartes and Newton and has brought us many great things, including modern science and increases in wealth, health and everyday living standards. Furthermore, it is so ingrained in our daily lives that we have forgotten it is a paradigm, not a fact. There are, however, some problems with it. First, there is no satisfactory explanation for why we have consciousness and experience meaning in our lives. Second, modern-day physics tells us that observations depend on characteristics of the observer at the large, cosmic, and small, subatomic scales. Third, ongoing humanitarian and environmental crises show us that our world is vastly interconnected. Our understanding of reality is expanding to incorporate these issues. In The Universe, Life and Everything . . . Dialogues on our Changing Understanding of Reality, some of the scholars at the forefront of this change, from the fields of physics, psychology, and social sciences, discuss the direction it is taking and its urgency.
1. What is reality? -- What is our current understanding of reality? -- What has been the approach? -- 2. Why do we need to expand our understanding of reality? -- Consciousness -- Modern-day physics: where "in with the new' does not mean "out with the old' -- We are part of life on our planet -- 3. Paradox of language -- Language may move away from meaning... -- ...But that does not make facts fictional -- 4. Is reality what we make it? -- Reality: just probabilities taking shape? -- Observer in the system -- Reality as a process -- 5. When efficient causation breaks down... Synchronicity and meaning -- Synchronicity in our daily lives -- Synchronicity in quantum mechanics -- Are our synchronous experiences quantum? -- Meaning and synchronicity in life -- 6. direction of change -- Reality as a stable process -- Directionality in reality -- Awareness as an inherent feature of reality -- nature of individual consciousness -- Integrating old wisdom into new thinking: the nature of greater consciousness -- 7. Conclusions and possible implications.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ontology; Metaphysics; Physics; Consciousness; Reality; Electronic books; Electronic books